Level of understanding of fitness instructors on injury prevention and treatment in Yogyakarta fitness center - Fatkurahman Arjuna; Furqon Hidayatullah; Sugiyanto Sugiyanto; Muchsin Douwes (LPMPP Universitas Negeri Yogyakarta, 2023)
A fitness instructor is critical in preventing severe injuries and providing the best care for members at fitness centers. This study aimed to discover whether fitness trainers’ understanding of injury prevention and treatment is related to the trainees’ injury histories. Furthermore, this study was also conducted to determine the fitness trainers’ understanding of preventing and treating injuries in fitness centers in the Special Region of Yogyakarta. This study is cross-sectional and applies a survey approach. The data collection technique utilized in this study was multiple-choice questions, with 70 trainers and their 233 trainees as the research subjects. The results showed that the fitness trainers’ understanding of injury prevention and treatment at the fitness center in the Special Region of Yogyakarta fell into the poor category. Meanwhile, the results showed that the fitness trainers’ understanding of injury prevention and treatment have a strong negative relationship with trainee’s injury histories (r = -0.700, p 0.001). The higher the fitness trainers’ understanding of injury prevention and treatment score obtained by the trainer, the lower the potential for the trainee to experience injury (Exp (B) 0.968 1). On the other hand, weekly trainee exercises have a good relationship with the trainees’ injury chances (p 0.001, Exp (B) 1.062 1). Thus, fitness trainers' injury prevention and treatment knowledge and weekly trainees exercise are strong predictors for predicting trainee's injury histories. Although other predictors were unable to predict trainee's injury histories in this study, we propose that these predictors may have potential.